Selenium Status of Southern Africa - Chilala, Pompido; Skalickova, Sylvie; Horky, Pavel (Nutrients, 2024)
Selenium is an essential trace element that exists in inorganic forms (selenite and selenates) and organic forms (selenoamino acids, seleno peptides, and selenoproteins). Selenium is known to aid in the function of the immune system for populations where human immunodeficiency virus (HIV) is endemic, as studies suggest that a lack of selenium is associated with a higher risk of mortality among those with HIV. In a recent study conducted in Zambia, adults had a median plasma selenium concentration of 0.27 μmol/L (IQR 0.14-0.43). Concentrations consistent with deficiency (<0.63 μmol/L) were found in 83% of adults. With these results, it can be clearly seen that selenium levels in Southern Africa should be investigated to ensure the good health of both livestock and humans. The recommended selenium dietary requirement of most domesticated livestock is 0.3 mg Se/kg, and in humans above 19 years, anRDA (recommended daily allowance) of 55 mcg Se/per dayisis recommended, but most of the research findings of Southern African countries have recorded low levels. With research findings showing alarming low levels of selenium in soils, humans, and raw feed materials in Southern Africa, further research will be vital in answering questions on how best to improve the selenium status of Southern African soils and plants for livestock and humans to attain sufficient quantities.
Keywords: dospělí; feed; humans; Humans; biofortification; zvířata; půda; Southern Africa; Africa, Southern; livestock; nutrition; selenium; Adult; food; Zambia; dobytek; jižní Afrika; Animals; lidé; selen; Livestock; Zambie; HIV infekce; HIV Infections; Selenium; Soil